Timing of formation of neoglacial landforms in the South Shetland Islands (Antarctic Peninsula): Regional and global implications. (15th April 2020) - Palacios, David; Ruiz-Fernández, Jesus; Oliva, Marc; Andrés, Nuria; Fernández-Fernández, José M.; Schimmelpfennig, Irene; Leanni, Laëtitia; González-Díaz, Benjamín; ,
Abstract: The timing of neoglacial advances in the Antarctic Peninsula (AP) is not yet well constrained. Accurate temporal reconstruction of Neoglaciation in the AP is needed to better understand past glacial responses and regional and global teleconnections during the Holocene. Here, we examine all available information about neoglacial advances in the South Shetland Islands (SSI) as well as in the broader geographical context of the AP region and Antarctic continent. In order to shed light on the contrasting chronologies existing for neoglacial advances in these regions, we focused on a case study where a detailed picture of the Holocene deglaciation was already available. Lake sediments revealed that Byers Peninsula, west of Livingston Island (SSI), was fully deglaciated during the Holocene Thermal Maximum. To complement this approach, we identified glacially polished bedrock surfaces, erratic boulders and a moraine ridge near the present front of the glacier in the SE corner. We applied cosmogenic ray exposure (CRE) dating using in situ 36 Cl for basalt rocks and 10 Be for granitic rocks in: (i) 8 samples from glacial erratic and ice-rafted boulders, (ii) 2 samples from moraine boulders, (iii) 2 samples from polished bedrock surfaces, and (iv) 1 sample from an erratic boulder deposited on one of these surfaces. The CRE dates indicate that the onset of deglaciation started around 9.9 ± 1.2 ka, with two phases of glacier expansion during the Mid-Late Holocene forming moraines at ∼4.1 ± 0.5 and ∼1.0 ± 0.2 ka, respectively. The main neoglacial advances in the AP and the SSI were mostly synchronous and coincided with cold periods, as shown by other records (e.g. glacio-isostatic marine terraces, marine and lake sediments). In addition, these periods of glacial expansion show a similar timing to those recorded in the Arctic. These results suggest that Neoglaciation was driven by global climate forcing in both polar areas despite temporal variations at regional and local scale. Highlights: The timing of neoglacial advances in the Antarctic Peninsula. Study case: Byers Peninsula, Livingston Island, South Shetland Islands. We applied cosmogenic ray exposure using 36Cl and 10Be isotopes. Deglaciation started around 9.9 ± 1.2 ka. Glacier expansion at ∼4.1 ± 0.5 and ∼1.0 ± 0.2 ka.